2010
DOI: 10.1093/jxb/erq235
|View full text |Cite
|
Sign up to set email alerts
|

UV radiation reduces epidermal cell expansion in leaves of Arabidopsis thaliana

Abstract: Plants have evolved a broad spectrum of mechanisms to ensure survival under changing and suboptimal environmental conditions. Alterations of plant architecture are commonly observed following exposure to abiotic stressors. The mechanisms behind these environmentally controlled morphogenic traits are, however, poorly understood. In this report, the effects of a low dose of chronic ultraviolet (UV) radiation on leaf development are detailed. Arabidopsis rosette leaves exposed for 7, 12, or 19 d to supplemental U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 51 publications
5
61
1
Order By: Relevance
“…130 The reduction in leaf size of UV-B exposed Arabidopsis plants has been associated to decrease in the cell expansion of the adaxial epidermal cells. 131 Jansen 105 found that the UV-B-induced reduction in plant growth, and more specifically in leaf area, has been attributed either to cell division or cell expansion or a combination of both. Some authors suggested that UV-B treatment reduced both the cell division and cell expansion in Pisum sativum, 71 Triticum aestivum, 132 & Trifolium repens.…”
Section: Staxen and Bornmanmentioning
confidence: 99%
“…130 The reduction in leaf size of UV-B exposed Arabidopsis plants has been associated to decrease in the cell expansion of the adaxial epidermal cells. 131 Jansen 105 found that the UV-B-induced reduction in plant growth, and more specifically in leaf area, has been attributed either to cell division or cell expansion or a combination of both. Some authors suggested that UV-B treatment reduced both the cell division and cell expansion in Pisum sativum, 71 Triticum aestivum, 132 & Trifolium repens.…”
Section: Staxen and Bornmanmentioning
confidence: 99%
“…However, available data about the effects of UV-B radiation on cell proliferation and cell expansion are contradictory, probably reflecting differences in experimental conditions. Acute, stress-inducing UV-B conditions cause necrosis and inhibit cell proliferation, while lower doses and/or chronic UV-B treatments affect both cell proliferation and expansion (Staxen and Bornman, 1994;Nogués et al, 1998;Laakso et al, 2000;Hopkins et al, 2002;Hofmann et al, 2003;Kakani et al, 2003;Hectors et al, 2007Hectors et al, , 2010Wargent et al, 2009a;Robson and Aphalo, 2012). For example, fewer epidermal cells were observed after UV-B exposure in some species (Gonzalez et al, 1998;Hopkins et al, 2002); however, stimulation of cell proliferation by UV-B radiation has also been reported in petunia (Petunia hybrida; Staxen and Bornman, 1994), and increases in leaf thickness attributed to increases in the number of parenchyma cells were reported in Brassica carinata and Medicago sativa (Bornman and Vogelmann, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Existing data on the effects of UV-B on cell proliferation and cell expansion are contradictory, probably reflecting differences in experimental conditions. Acute, stress-inducing UV-B conditions usually inhibit cell proliferation, while both cell proliferation and expansion are affected by lower doses and/or chronic UV-B treatments (Staxen and Bornman, 1994;Nogués et al, 1998;Laakso et al, 2000;Hopkins et al, 2002;Hofmann et al, 2003;Kakani et al, 2003;Hectors et al, 2007Hectors et al, , 2010Wargent et al, 2009;Robson and Aphalo, 2012). For example, the number of epidermal cells at maturity decreased after UV-B exposure in some species (Gonzalez et al, 1998;Hopkins et al, 2002); on the contrary, in lettuce (Lactuca sativa) leaves, UV-B reduced cell expansion rate and final leaf size (Wargent et al, 2009).…”
mentioning
confidence: 99%